Electronality revisited. Autism and the production of meaning in our time - Reaño, Ernesto (2023)
The theory of electronality, born from literary and semiotic studies has been used since 2017 to understand the functioning of the autistic mind. This article updates concepts and terminology resulting from research and practice in daily work with autistic people in EITA - Peru. Autism is a life condition associated with an atypical neurodevelopment (neurotype) where talent is appreciated in the areas of information systematization, detailed processing and pattern search. The form of production of meaning in our current society -still in transit from the scribal to the electronal stage- finds similarities with the way in which the autistic mind processes and perceives information from the world, privileging subjectivity over the objective, the deferred communication rather than immediate and the use of extensional logic rather than intensional. This does not mean that new technologies favor the appearance of autism since it is not caused by external influences, it means that there is a link between the culture of cybernetics and the culture of autism. Thus, to know it is to understand our similarity and how to inhabit this stage of arrival in the electronal society.